2020
DOI: 10.3390/diagnostics10010046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Activity of Daily Life in Mucopolysaccharidosis Type II Patients with Hematopoietic Stem Cell Transplantation

Abstract: The effectiveness of hematopoietic stem cell transplantation (HSCT) for mucopolysaccharidosis type II (MPS II, Hunter disease) remains controversial although recent studies have shown HSCT provides more clinical impact. This study aims to evaluate the long-term effectiveness of HSCT using the activity of daily living (ADL) scores in patients with MPS II. Sixty-nine severely affected MPS II patients (19 patients who received HSCT and 50 untreated patients) and 40 attenuated affected patients (five with HSCT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Improved [192,[199][200][201][202][203][204][205] Improved [206,207] Improved (case studies n < 10) [208][209][210]…”
Section: Manifestation Ert Hsct Hepatosplenomegalymentioning
confidence: 99%
See 2 more Smart Citations
“…Improved [192,[199][200][201][202][203][204][205] Improved [206,207] Improved (case studies n < 10) [208][209][210]…”
Section: Manifestation Ert Hsct Hepatosplenomegalymentioning
confidence: 99%
“…No change [199,200] Improved (shoulders) [195,205] No change [206] No change (case studies n < 10) [214,216,218,219] Improved [207,220] Improved (case studies n < 10) [208,209,213]…”
Section: Joint Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also employed in smaller numbers of patients with MPS II, III, IV and VI with controversial results [4][5][6][7][8][9][10][11][12][13]. Recent evidence suggests HSCT as an acceptable treatment option for MPS II [12][13][14]. Enzyme replacement therapy (ERT) is the other more recent available treatment, which is obtained through recombinant DNA technology.…”
Section: Introductionmentioning
confidence: 99%
“…Experience with HSCT in MPS II is limited, but recent studies have demonstrated some efficacy in terms of reducing GAG levels, and improving some of the somatic manifestations such as coarse facial features, joint stiffness, hearing defects, hernia, hepatosplenomegaly and heart valve disorders. In addition, improvements in activities of daily living and the frequency of respiratory infections have also been reported 2,27–30 . There is also preliminary evidence of modest neurological benefit with HSCT in MPS II patients, which has not been evident with ERT 28,29 …”
Section: Mucopolysaccharidoses: a Rare And Heterogeneous Group Of Mulmentioning
confidence: 98%